2008
DOI: 10.1063/1.2901879
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring magnetic anisotropy at the ferromagnetic/ferroelectric interface

Abstract: It is predicted that magnetic anisotropy of a thin magnetic film may be affected by the polarization of a ferroelectric material. Using a Fe∕BaTiO3 bilayer as a representative model and performing first-principles calculations, we demonstrate that a reversal of the electric polarization of BaTiO3 produces a sizable change in magnetic anisotropy energy of Fe films. Tailoring the magnetic anisotropy of a nanomagnet by an adjacent ferroelectric material may yield entirely new device concepts, such as electric-fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
123
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 145 publications
(134 citation statements)
references
References 32 publications
10
123
1
Order By: Relevance
“…Such complex interplay between the spin (magnetism), lattice (strain), charge (electrostatic) and orbit (e.g. charge-driven interfacial orbital hybridization [45][46][47][48][49][50] or reconstruction [51][52][53][54][55]) across the interface of the multiferroic heterostructure would be a very interesting but tough issue. -The mesoscale mechanism of such voltage-controlled magnetism in multiferroic heterostructures is also important.…”
Section: Discussionmentioning
confidence: 99%
“…Such complex interplay between the spin (magnetism), lattice (strain), charge (electrostatic) and orbit (e.g. charge-driven interfacial orbital hybridization [45][46][47][48][49][50] or reconstruction [51][52][53][54][55]) across the interface of the multiferroic heterostructure would be a very interesting but tough issue. -The mesoscale mechanism of such voltage-controlled magnetism in multiferroic heterostructures is also important.…”
Section: Discussionmentioning
confidence: 99%
“…First-principles calculations of the Fe/BaTiO 3 bilayer have shown that a reversal of the electric polarization of BaTiO 3 produces a sizeable change in the surface MCA energy of the Fe film [137].…”
Section: (B) Surface Magnetocrystalline Anisotropymentioning
confidence: 99%
“…22 Alternatively, the interface magnetic anisotropy (and hence the magnetization orientation) may be tailored electronically by the ferroelectric polarization of an adjacent ferroelectric film. 23,24 This approach has a number of advantages. First, the effective electric field induced by the polarization charge at the interface may reach 1 GV/m, i.e., be much higher than the electric field produced in laboratory conditions.…”
mentioning
confidence: 99%